A Wireless ECG Device with Mobile Applications for Android - Mohamad Hafis Nornaim; Nurul Ashikin Abdul-Kadir; Fauzan Khairi Che Harun; Mohd Azhar Abdul Razak (Proceeding of the Electrical Engineering Computer Science and Informatics, 2020)
Electrocardiograph (ECG) is a measuring device that used in hospital to monitor electrical activity of heart. Commonly used ECG device is a Holter monitor, a portable and wired device, which is bulky and not suitable for measuring and recording athlete's heart activity during training. The objective of this study was to design the ECG monitoring system as an Internet of Things (IoT) device, equipped with a temperature detector to detect user's body temperature. The ECG signals and the temperature were transmitted wirelessly using Bluetooth transmission to the mobile applications (apps). Both signals were set to display on mobile apps which was developed using Blynk application. At the end of this project, the signals were shown on the mobile apps and the user could monitor their own ECG signals as well as to share with their caretaker or physician later.